De vítimas a Rés: uma análise do controle punitivo sobre os corpos femininos. - Silva, Joane Marcelle de Oliveira e (2020)
The rate of female incarceration in the country has grown by 656% in the last 16 years, with the crime of drug trafficking persisting as an incarcerator par excellence, insofar as 59.98% of imprisoned women account for this classification. When the proportional numbers are observed, it can be seen that the state of Alagoas had a 444% increase in the rate in question between the years 2007 and 2014, which means an increase of 194% in relation to the male indexes. It is, therefore, this scenario that justifies the need for a better understanding of the performance of the Criminal Justice System under the bodies of women in Maceió / AL. In this sense, with the objective of understanding the experience of these women, the present work analyzed all the processes coming from the 15th Criminal Court of the Capital / Narcotics Court of Maceió / AL that have Defendants, dated from the years 2013, 2014, 2015, 2016 and 2017 and compared the results found with those from the Propositional Analytical Report “Between Retributive and Restorative Practices: the Maria da Penha Law and the Advances and Challenges of the Judiciary”, to conclude that the profile of women crossed by the Criminal Justice System in Maceió / AL - whether as a Defendant or Victim - coincides in several aspects, as well as that the state penal apparatus not only fails to achieve the purposes for which it is proposed, but has the ability to intensify the pain and suffering previously faced by these women.